Qualitative Assessment of the 4P Marketing Mix for Modified Resistance Bands in the Indonesian Martial Arts Industry - Lydia Karnadi; Andamar Pradipta; Muhammad Bagus Darmawan (Journal of Strategic Innovation and Business Management, 2025)
This study qualitatively assesses the suitability and market acceptance of a modified resistance band product tailored for the rapidly expanding martial arts sector in Indonesia. It investigates the efficacy of a proposed 4P-marketing mix strategy (Product, Price, Place, Promotion) in meeting the unique demands of Indonesian martial arts practitioners. Utilizing secondary data for an initial market assessment, the research proceeds with a qualitative market research approach. In-depth interviews were conducted with 20 purposively sampled respondents, martial arts practitioners in Indonesia. The interview results were analyzed using thematic analysis methodologies to identify patterns and insights regarding the product's design, distribution preferences, price sensitivity, and promotion effectiveness. The study reveals that the developed 4P-marketing mix generally aligns with market demands. However, a notable mismatch was identified in the pricing strategy, as most respondents expect a more affordable price, ideally between Rp 100,000 and Rp 150,000 for a modified resistance band set. This research offers timely qualitative insights into the niche market of martial arts equipment in a developing economy like Indonesia. It provides practical recommendations for refining marketing strategies for new product launching and contributes theoretically by examining the dynamic application of the 4P-marketing mix in a context characterized by unique digital adoption patterns and price sensitivities.